2014
DOI: 10.1007/s10969-014-9171-4
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic acids in crystallization of macromolecules: learning from successful crystallization experiments

Abstract: The production of macromolecular crystals suitable for structural analysis is one of the most important and limiting steps in the structure determination process. Often, preliminary crystallization trials are performed using hundreds of empirically selected conditions. Carboxylic acids and/or their salts are one of the most popular components of these empirically derived crystallization conditions. Our findings indicate that almost 40 % of entries deposited to the Protein Data Bank (PDB) reporting crystallizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Crystallization experiments were performed at room temperature using the sitting-drop vapor-diffusion method in 96-well sitting-drop plates (Molecular Dimensions, Alamonte Springs, Florida, USA). A solution of recombinant BtDapA was mixed with well solution from a custom carboxylic acid screen (Offermann et al, 2014). Crystals were grown in 0.1 M succinate pH 7.0, 0.1 M acetate, 0.8 M NaCl, 10 mM 5-aminoisophthalic acid, 15%(w/v) PEG 3350.…”
Section: Btdapa Production and Crystallizationmentioning
confidence: 99%
“…Crystallization experiments were performed at room temperature using the sitting-drop vapor-diffusion method in 96-well sitting-drop plates (Molecular Dimensions, Alamonte Springs, Florida, USA). A solution of recombinant BtDapA was mixed with well solution from a custom carboxylic acid screen (Offermann et al, 2014). Crystals were grown in 0.1 M succinate pH 7.0, 0.1 M acetate, 0.8 M NaCl, 10 mM 5-aminoisophthalic acid, 15%(w/v) PEG 3350.…”
Section: Btdapa Production and Crystallizationmentioning
confidence: 99%
“…Besides the above-mentioned bias of sparse matrix screens, additional drawbacks come from the mode of use: usually, all the conditions in the screens are used, even when there is prior knowledge that a specific condition or factor is detrimental. In one of the surveys on crystallization conditions, Fazio et al 9,10 showed that the collection of successful compounds has changed in the past decade and that commercial screens sparsely cover some of these crystal yielding conditions. A similar conclusion was drawn by Gorrec 11 who showed that the 1440 crystallization conditions routinely used in the crystallization facility at MRC Laboratory of Molecular Biology (MRC-LMB, Cambridge, UK)) under-sample the chemical space.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the surveys on crystallization conditions, Fazio et al , showed that the collection of successful compounds has changed in the past decade and that commercial screens sparsely cover some of these crystal yielding conditions. A similar conclusion was drawn by Gorrec who showed that the 1440 crystallization conditions routinely used in the crystallization facility at MRC Laboratory of Molecular Biology (MRC-LMB, Cambridge, UK)) under-sample the chemical space.…”
Section: Introductionmentioning
confidence: 99%
“…In the article by Luft and coworkers, the 'mini-phase diagram' approach to initial crystallization suggests using chemicals that have already been proven to be successful in protein crystallization at concentrations that have already been successful (Chan et al, 2013;Luft et al, 2014). Analyses of the most common chemicals used in crystallization have been performed before (Peat et al, 2005;Lu et al, 2012;Parker & Newstead, 2012;Offermann et al, 2014), and we wondered whether the conclusions from these earlier studies still hold today.…”
Section: Introductionmentioning
confidence: 99%